2022
DOI: 10.3389/fmicb.2021.825743
|View full text |Cite
|
Sign up to set email alerts
|

Arginine GlcNAcylation and Activity Regulation of PhoP by a Type III Secretion System Effector in Salmonella

Abstract: Salmonella type III secretion system (T3SS) effector SseK3 is a glycosyltransferase delivered directly into the host cells to modify host protein substrates, thus manipulating host cellular signal transduction. Here, we identify and characterize the Arg-GlcNAcylation activity of SseK3 inside bacterial cells. Combining Arg-GlcNAc protein immunoprecipitation and mass spectrometry, we found that 60 bacterial proteins were GlcNAcylated during Salmonella infection, especially the two-component signal transduction s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…The work described here provides the first evidence that Arg-glycosylation of the bacterial transcription factor NagC by SseK1 increases NagC affinity for DNA. These data also represent, to our knowledge, along with the recently described work regarding Arg-glycosylation of PhoP by SseK3 19 , the first example of a T3SS effector directly regulating gene expression by modifying a transcription factor. Future experiments aiming to solve the co-crystal structure of an Arg-GlcNac-NagC-DNA complex may permit a molecular understanding of how Arg-glycosylation of transcription factors alters their interactions with DNA.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The work described here provides the first evidence that Arg-glycosylation of the bacterial transcription factor NagC by SseK1 increases NagC affinity for DNA. These data also represent, to our knowledge, along with the recently described work regarding Arg-glycosylation of PhoP by SseK3 19 , the first example of a T3SS effector directly regulating gene expression by modifying a transcription factor. Future experiments aiming to solve the co-crystal structure of an Arg-GlcNac-NagC-DNA complex may permit a molecular understanding of how Arg-glycosylation of transcription factors alters their interactions with DNA.…”
Section: Discussionsupporting
confidence: 72%
“…To some extent, these results are counter-intuitive, because one might reasonably expect that glycosylating a basic amino acid would tend to reduce protein affinity for DNA. We also note that, in a related system, the recent analysis of SseK3 glycosylation of PhoP concluded that there was a slight reduction in PhoP affinity for DNA as a function of PhoP R215 glycosylation, although the binding affinities were not calculated 19 . However, it is not clear from these studies whether the investigators used phosphorylated PhoP or recombinant, non-phosphorylated PhoP for their EMSAs, a variable which might affect the interpretation of these data.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The protein samples for LC-MS/MS analysis were prepared according to the protocols described previously with minor modifications ( Xue et al, 2022 ). Specifically, the protein sample (50 μg, qualified by optical density at 260 nm) was denatured by adding one-fourth 8M urea (Aladdin, China).…”
Section: Methodsmentioning
confidence: 99%
“…The digested peptide samples were analyzed using a Q Exactive Plus mass spectrometer and an EASY nano Liquid chromatography (EASY nLC 1200, Thermo Scientific) with an EASY nanoelectrospray interface according to the methods described before ( Xue et al, 2022 ). The nano liquid chromatography system was equipped with a Thermo Scientific Acclaim Pepmap nano-trap column (C18, 5 μm, 100 Å, 100 μm × 2 cm) and a Thermo Scientific EASY-Spray column (Pepmap RSLC, C18, 2 μm, 100 Å, 50 μm × 15 cm).…”
Section: Methodsmentioning
confidence: 99%